Qualitative Inquiry: A Personal Experience Doing Narrative and Discursive Approach in Relation to Religious Issues - Md. Yusoff, Yusmini (Jurnal Usuluddin, 2017)
This article presented an account of the author positioning with the research method and the data texts. It describes the way the author used narrative and discourse analytic inquiry to identify and explore instances of discursive practices in research participants’ speaking, as well as the research process and techniques.